Pengembangan LKPD Berbasis Etnomatematika Permainan Tradisional Congklak untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SMP - Nicky Nastity Cahya Ningrum; Ucik Fitri Handayani (Mandalika Mathematics and Educations Journal, 2026)
Mathematics learning at the junior high school level is still predominantly abstract and has not sufficiently connected mathematical concepts with real-life contexts and local culture, resulting in students’ critical thinking skills not developing optimally. One effort to address this issue is through the development of contextual and meaningful ethnomathematics-based teaching materials. This study aims to develop an ethnomathematics-based Student Worksheet (LKPD) using the context of the traditional congklak game to improve junior high school students’ critical thinking skills. This research employed a research and development approach using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects were ninth-grade students of SMP Negeri 5 Satu Atap Sumbermanjing Wetan, selected through purposive sampling. Data were collected through expert validation, teacher and student response questionnaires, as well as pretest and posttest instruments. The expert validation results showed that the developed LKPD obtained a validity percentage of 85.3%, categorized as very valid. The practicality test results indicated percentages of 93.33% from teachers and 82.4% from students, categorized as very practical. The effectiveness test using a paired sample t-test revealed a Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant improvement in students’ critical thinking skills after the implementation of the LKPD. Therefore, the ethnomathematics-based LKPD with the congklak game context is valid, practical, and effective in enhancing students’ critical thinking skills.